Elisabeth R. Geleerd papers - Geleerd, Elisabeth R. (Elisabeth Rozetta), 1909-1969.
Correspondence, memorandum, mss. of articles and speeches, reports, lecture notes, patient case files, financial and legal papers, photographs, and other papers pertaining primarily to Geleerd's career as a psychoanalyst. Includes material pertaining to her psychoanalytic practice in New York, N.Y.; her involvement in the American Psychoanalytic Association, the New York Psychoanalytic Institute, and the New York Psychoanalytic Society, especially in the areas of child analysis and of educational and professional standards for analysts; and her writings on various psychoanalytic topics. Also includes a small amount of material relating to Geleerd's work at the Menninger Clinic and the Southard School, Topeka, Kansas.
Correspondents include Princess Marie Bonaparte, Dorothy T. Burlingham, Anna Freud, Marjorie Harley, Otto Isakower, Ernest Jones, Robert P. Knight, Margaret Mead, Karl Menninger, William C. Menninger, and Geleerd's husband, psychoanalyst, Rudolph Maurice Loewenstein.
Psychoanalyst.
Collection material in English, Dutch, and German.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Sigmund Freud collection.
Keywords: Bonaparte, Marie, -- Princess, -- 1882-1962 -- Correspondence; Burlingham, Dorothy T. -- Correspondence; Freud, Anna, -- 1895-1982 -- Correspondence; Harley, Marjorie. -- Correspondence; Isakower, Otto, -- 1899-1972 -- Correspondence; Jones, Ernest, -- 1879-1958 -- Correspondence; Knight, Robert P. -- 1902-1966 -- Correspondence; Loewenstein, Rudolph Maurice -- Correspondence; Mead, Margaret, -- 1901-1978 -- Correspondence; Menninger, Karl A. -- 1893-1990 -- Correspondence; Menninger, William Claire, -- 1899-1966 -- Correspondence; American Psychoanalytic Association; Menninger Clinic; New York Psychoanalytic Institute; New York Psychoanalytic Society; Southard School; Child analysis; Psychoanalysis; Psychoanalysis -- Societies, etc; Psychoanalysis -- Standards; Psychoanalysis -- Study and teaching; Psychoanalysts